Menjaga Kesehatan Mental Keluarga saat Pembatasan Sosial Berskala Besar pada Masa Pandemi Covid-19 - Dian Furwasyih; Sunesni Sunesni; Yulia Arifin; Rahmayeni Supri; Widya Zalmawita; Miftah Dwi Riska (LPPM Akbid Harapan Ibu Pekalongan, 2021)
The outbreak of the COVID-19 coronavirus infection that has spread throughout the world has had a major impact on the health of the global community, including mental health. Stress that arises during the COVID-19 pandemic could be in the form of fear and anxiety about personal health and the health of other loved ones, changes in sleep and diet patterns, aggravating physical conditions, especially in someone with chronic illness. This activity is one solution that is expected to broaden the audience's insight about maintaining the mental health of families during the COVID-19 pandemic. This activity is carried out through CISCO WEBEX Meeting media. The outputof this activity was the increase of level of knowledge of the audiences 37.5%, the publication of activities on youtube media and publication articles in a journal.